Multicentric study of epidemiological and clinical characteristics of persons injured in motor vehicle accidents in Medellín, Colombia, 2009-2010 (Colombia Medica, 2013)
Introduction: Traffic accidents (TA) cause 1.23 million deaths each year worldwide while between 20 and 50 million persons are injured each year. In 2011 in Medellin, Colombia, there were 307 traffic deaths and 23,835 injured with 411 accidents for each 10,000 vehicles.Objective: The purpose of the study was to describe the epidemiologic and clinical characteristics, as well as the quality of life and disability outcomes for those injured in traffic accidents in Medellin.Methods: This prospective, descriptive, cross-sectional study collected data from 834 patients that were classified with the New Injury Severity Score (NISS) , the WHODAS-II (Disability Assessment) Scale and the SF-36 Health Survey.Results: Three-fourths (75.8%) of the patients were male. Eightyone percent of patients were involved in motorcycle accidents, with 45.6% suffering moderate trauma, and 32.6% experiencing severe trauma. Of the patients with severe trauma, 8.5% were not wearing helmets. Half of the sample (49.7%) injured their extremities. The WHODAS-II domains most affected were: Activities outside the home (62.0 %), Housework (54.3%) and Moving in one’s environment (45.2 %). Quality of life areas affected were: Physical role (20.3%), Body pain (37.3 %) Emotional role (44.1%), Physical functioning (52.6 %).Conclusions: Patients with more severe injuries had higher levels of disability and a worse quality of life. Motorcycles made up a large proportion of traffic accidents in this city and mitigation strategies to reduce this public health problem should particularly focus on this high-risk group.